2014
DOI: 10.12659/msm.889786
|View full text |Cite
|
Sign up to set email alerts
|

Classifications of clinical and bowel morphological changes and their relationship with characteristics of patients with incarcerated groin hernias

Abstract: BackgroundThere is currently no grading standard for the degree of clinical and bowel morphological changes. The objective of this study was to define clinical and bowel morphological classifications and investigate the possible relationship with the characteristics of patients with incarcerated groin hernias.Material/MethodsWe retrospectively studied 195 patients who underwent emergency hernia repair with simultaneous bowel resection between January 1992 and January 2012. We classified the degree of clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…They also found that outcomes were worse in older patients, especially those with comorbidities and higher ASA scores. 312 …”
Section: Emergency Treatment Of Groin Herniamentioning
confidence: 99%
“…They also found that outcomes were worse in older patients, especially those with comorbidities and higher ASA scores. 312 …”
Section: Emergency Treatment Of Groin Herniamentioning
confidence: 99%